Study of salinity effects on the inorganic phosphorus transformation in three different soil series of Ganges River Floodplain - Nasrin, Sonia; Biswas, Tanmoy Kumar; Amin, Md Sadiqul; Khatun, Monowara (Jahangirnagar University Journal of Biological Sciences, 2016)
The present study was carried out to investigate the effects of salinity level on different forms of inorganic phosphorus (P) transformation in three different soil series such as Amjhupi, Gopalpur and Bajoa located in Ganges River Floodplain. Two non-saline soils and one slightly saline soil with different textural classes were collected from these sites. The salinity treatments were 0, 6, 10 and 13 dSm-1 with three replications. The treated soils were then incubated in laboratory at field capacity moisture condition. To determine the transformation of different forms of inorganic P, sampling was done for 0, 14, 21, 42 and 84 days. Different forms of inorganic P such as soluble and exchangeable phosphorus (SE-P), iron and aluminium bound phosphorus (Fe and Al-P), calcium bound phosphorus (Ca-P) and residual phosphorus (RE-P) were determined. For Amjhupi soil series, the sequence of different forms of inorganic P was RE-P>Ca-P>Fe and Al-P>SE-P according to their amount. For Gopalpur and Bajoa soil series, the sequence was Ca- P>RE-P>Fe and Al-P>SE-P and RE-P>Ca-P>Fe and Al-P>SE-P, respectively. The sequence clearly indicates that the soluble and exchangeable P decreases with time due to salinity which reduces the uptake of P and ultimately reduces the yield. The changes were statistically significant (p<0.0001) in case of all three soils. Jahangirnagar University J. Biol. Sci. 5(1): 71-79, 2016 (June)